Modifying the Dual Crop Coefficients with Leaf Area Index and Meteorological Factors to Improve the Estimated Evapotranspiration from Maize Fields - YAO Tingyue; WANG Yining; SHI Leitao; ??; ZHOU Chao; JU Qin; WANG Zhenlong (Guan'gai paishui xuebao, 2023)
【Objective】 Evapotranspiration consists of plant transpiration (Tr) and soil surface evaporation (Es); It is a critical component in the hydrological cycle, often estimated using meteorological and plant data. We present a modified method in this paper to improve its calculation. 【Method】 The method was based on the Penman-Monteith (P-M) equation using the dual crop coefficients as recommended by FAO-56. The methods for calculating the base crop coefficient (Kcb) and soil evaporation coefficient (Ke) in the equation are modified using the leaf area index (LAI), meteorological factors and soil water content. The modified model is then used to estimate real evapotranspiration (ETc) from the reference crop evapotranspiration (ET0) calculated from the P-M model. We test the model against data measured in 2018—2019 from large scale lysimeters grown with summer maize at the Wudaogou Hydrological Experimental Station in Anhui province. 【Result】 The modified dual crop coefficient model improved the accuracy of the estimated evapotranspiration, with the estimated average daily evapotranspiration being 4.89 mm/d (the measured was 4.66 mm/d) in 2018, and 5.72 mm/day (the measured was 5.67 mm/d) in 2019. The R2, RMSE, Ens and AAE of the modified model were 0.89, 0.98 mm/d, 0.86 and 0.73 mm/d, respectively, in 2018; and 0.89, 0.76 mm/d, 0.89 and 0.58 mm/d, respectively, in 2019. 【Conclusion】 The modified dual crop coefficient method is robust and improves the accuracy of the estimated evapotranspiration from summer maize fields, compared with the traditional method.